2021
DOI: 10.1371/journal.pone.0257242
|View full text |Cite
|
Sign up to set email alerts
|

The impact of active case finding on transmission dynamics of tuberculosis: A modelling study

Abstract: Background In the last decade, active case finding (ACF) strategies for tuberculosis (TB) have been implemented in many diverse settings, with some showing large increases in case detection and reporting at the sub-national level. There have also been several studies which seek to provide evidence for the benefits of ACF to individuals and communities in the broader context. However, there remains no quantification of the impact of ACF with regards to reducing the burden of transmission. We sought to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to the WHO, two important community-based interventions that can help reduce the burden of neglected tropical diseases are the implementation of ACF campaigns and mass prophylaxis [ 22 ]. Furthermore, the WHO demonstrated that the ACF program is effective in reducing TB in the short term and can substantially reduce patient-incurred costs, which contribute to the end-TB strategy target [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, two important community-based interventions that can help reduce the burden of neglected tropical diseases are the implementation of ACF campaigns and mass prophylaxis [ 22 ]. Furthermore, the WHO demonstrated that the ACF program is effective in reducing TB in the short term and can substantially reduce patient-incurred costs, which contribute to the end-TB strategy target [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the best timing to efficiently measure the impact on TB-infection rates after an intervention has been introduced. Modelling studies on active case finding suggest it might take several years before the impact is noticeable [36]. In our study, the cohort of AYA was enrolled approximately 18 months after the PopART intervention (that was delivered for four years) ended.…”
Section: Plos Global Public Healthmentioning
confidence: 98%